Productive moisture stock assessment in the apple orchards soils of forest steppe north - Zakharov, V L; Morgacheva, N V; Petrisheva, T Yu (IOP conference series. Earth and environmental science, 2020)
The research was carried out in the north of forest steppe zone of Russia. The research subjects are soils under which apple trees of fruit-bearing age are located (16-24 years). Over the years of the research 50 soil cuts were laid in the apple orchards. United soil samples were formed by mixing the samples from near-stalk stripes and row-spacing. The total depth of searched cuts was 220 m. All the soil moisture capacity categories were determined by thermostat weight method: maximum water adsorption after airy dry soil condition in desiccators at air humidity close to 100%, limit field or the least soil moisture capacity after moist soil condition on the plaster casts and after free gravitational moisture coming down the profile on the flooded areas, the capillary bonding breakage humidity by multiplication of limit field soil moisture capacity and coefficient of 0.6. The total moisture stock was calculated as multiplication of soil density, layer thickness and limit field soil moisture capacity. Remote moisture stock was calculated as multiplication of soil density, layer thickness, maximum water adsorption and coefficient of 1.37. It was established that limit field soil moisture capacity significantly varies not only within one searched farm but inside soil type and soil subtype. Productive moisture stock in spring in ploughing soil layer occupied by the apple orchids of forest steppe north are described as good and represent 406-720 m3/ha (41-72 mm). Productive moisture stock in one-meter soil layer of apple orchards are assessed as very good and vary from 2993 to 4822 m3/ha (293-482 mm). According to productive moisture stock increasing in a meter layer apple orchards soils of forest steppe north can be placed in the following order: podzolic chernozem < chernozem moist meadow < grey forest < chernozem meadow < typical chernozem < leached chernozem < meadow chernozem < meadowish chernozem.